Designing a resilience-based intervention program for children with cancer and their families: a study protocol - Simard, Chantale; Roberge, Véronique; St-Pierre, Maxime; Cherblanc, Jacques; Bergeron-Leclerc, Christiane; Kadri, Mohamed Abdelhafid; Lacharité, Carl; Bérubé, Samuel; Lapointe, Laurie; Faucher, Valérie; Dufresne, Sebastien S. (Frontiers in Psychology, 2024)
Background: Advances in pediatric oncology have significantly increased survival rates, yet have introduced challenges in managing long-term treatment side effects. This study process introduces an interdisciplinary clinical intervention program rooted in the family resilience framework, aimed at improving well-being across the cancer trajectory for children and their families, especially those in Canadian communities far from specialized oncology centers with limited access to resources. challenges, are adapted to the unique contexts of communities distant from specialized cancer treatment centers. A mixed-methods approach will evaluate program effectiveness.Expected Results: Anticipated outcomes include the empowerment of families with self-management tools and professional support, designed to mitigate biopsychosocial and spiritual complications. By addressing the specific needs and limitations of these communities, the program strives to improve the overall health and well-being of both undergoing treatment and survivorship phases.Discussion: By focusing on comprehensive care that includes both professional interventions and self-management, this initiative marks a significant shift towards a holistic, family-centered approach in pediatric oncology care for remote communities. It underlines the necessity of accessible interventions that confront immediate and long-term challenges, aiming to elevate the standard of care by emphasizing resilience, professional support, and family empowerment in underserved areas.